Mekanisme Pencairaan Klaim Badan Penyelenggara Jaminan Sosial (BPJS) Ketenagakerjaan Jaminan Hari Tua di Tengah Pandemi Covid-19 - Kadek Yuda Kumala T.D; Anak Agung Sagung Laksmi Dewi; Ni Made Puspasutari Ujianti (Fakultas Hukum, Universitas Warmadewa, 2021)
For humanity, the right of Indonesian citizens to work and livelihood must be guaranteed. Employment issues are related to the creation of a business climate, security, stability, policies, and laws and regulations, at the local and national levels. It can be a motivating factor or an obstacle at work. The purpose of this study is to find out the legal arrangements for filing claims for BPJS Employment Old Age Security at Prima Medika Hospital Denpasar and to find out the obstacles faced in the claim process for BPJS Employment Old Age Security at Prima Medika Hospital Denpasar. The type of empirical research is the case approach method, and the data collection techniques are interviews and document studies. The results of the study are basically Government regulations No. 46 of 2015 concerning the Implementation of Old Age Guarantees. The program is a cash benefit that is given when you have entered a certain age, do not want to work again, are completely disabled so they cannot work again or die and will be given until the time limit after a minimum of ten years of participation. Lack of natural resources to provide services to claim participants, so that the services provided are also not effective, and the lack of socialization of BPJS Employment on all matters relating to the implementation of Old Age Security.